Age structure, recruitment variation, and sex ratio in blue cod ( Parapercis colias ) subpopulations in New Zealand - Michael Peter Beentjes (New Zealand Journal of Marine and Freshwater Research, 2021)
Age compositions from eight blue cod ( Parapercis colias ) subpopulations off the South Island of New Zealand were compared to investigate recruitment patterns temporally and spatially. Findings indicate (1) recruitment is highly variable between years, (2) subpopulations closer to each other have similar age compositions, and (3) strong and weak recruitment events are linked and the key processes that drive recruitment strength are acting on a large spatial scale. Recruitment variability among years and similarities between areas are likely to be density‐independent, due to environmental fluctuations. Age compositions exhibited modal progression of age classes providing validation of ageing based on counts of rings on otoliths. Sex ratio by age and length were compared in relation to their reproductive strategy of changing sex from female to male (protogynous hermaphrodites). Sex ratio pattern differed for each of the eight subpopulations but was most similar in those from the same area. Males dominate at younger ages and sex ratio swings in favour of females with increasing age. Patterns in sex ratio with size are virtually the opposite to those of age because the largest fish are invariably males. These results support the theory that the form of protogyny in blue cod is diandric.